EKGViewExplorer: Uma Ferramenta para Exploração dos Dados e Metadados da Visão Semântica em Enterprise Knowledge Graphs - Freitas, José Renato S.; Vidal, Vânia P.; Rolim, Tulio V.; Arruda, Narciso (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais Estendidos do XL Simpósio Brasileiro de Bancos de Dados, 2025)
The semantic view of an Enterprise Knowledge Graph (EKG) offers a semantically coherent, integrated perspective over an organization’s heterogeneous data sources. This paper presents EKGViewExplorer, an interactive graphical tool that allows users to navigate both the data and metadata in EKGs built with the DDP SV, a data design pattern that logically organizes semantic view data and metadata into a four-level hierarchy, enabling scalable maintenance and context-aware exploration. At the heart of this architecture lies the metadata graph, encoded with the VoSV vocabulary, which captures detailed, machine-readable information about structure, provenance, and quality of semantic view. By coupling intuitive exploration capabilities with comprehensive metadata capture, EKGViewExplorer empowers data stewards and domain experts to understand, validate, and evolve enterprise semantic views more effectively.